2010
DOI: 10.1097/sap.0b013e3181d6e2f2
|View full text |Cite
|
Sign up to set email alerts
|

Suprathel–Acetic Acid Matrix Versus Acticoat and Aquacel as an Antiseptic Dressing

Abstract: Our results support the notion, that the Suprathel-acetic acid matrix has an excellent bactericidal effect and therefore seems to be suitable as a local antiseptic agent in the treatment of burn wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
(16 reference statements)
1
19
0
2
Order By: Relevance
“…These properties may theoretically minimize the risk of wound colonization and wound infection and may, therefore, support optimal reepithelialization. However, an in vitro study by Ryssel et al showed insufficient evidence for an antiseptic effect of Suprathel ® [28]. Our study seems to support these results since the number of patients with a colonized wound did not decrease after application of Suprathel ® .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These properties may theoretically minimize the risk of wound colonization and wound infection and may, therefore, support optimal reepithelialization. However, an in vitro study by Ryssel et al showed insufficient evidence for an antiseptic effect of Suprathel ® [28]. Our study seems to support these results since the number of patients with a colonized wound did not decrease after application of Suprathel ® .…”
Section: Discussionsupporting
confidence: 79%
“…Suprathel ® forms a surrogate, natural barrier for microorganisms, that is intended to prevent accumulation of wound exudate and contains polylactic acid which reduces the local wound pH [28]. These properties may theoretically minimize the risk of wound colonization and wound infection and may, therefore, support optimal reepithelialization.…”
Section: Discussionmentioning
confidence: 99%
“…Another feature that is attributed to the temporary skin substitute is its antiseptic effect . Although the material actually reduces the local wound pH due to its polylactide‐acid properties, a bactericidal effect could not be found in vitro . The same group reported a much more relevant in vitro antimicrobial potential for the temporary skin substitute in combination with acetic acid, an antiseptic agent featuring bactericidal properties .…”
Section: Discussionmentioning
confidence: 99%
“…Topical medications such as boric acid, acetic acid, 3% citric acid, 0.5% chlorhexidine acetate (Bactigrass), silver-coated dressing (Acticoat), and 1% silver sulfadiazine (Silverdin) have been used to treat burn wounds infected with Pseudomonas aeruginosa. [12][13][14][15][16]18,19,25,27 However, no study has compared the effectiveness of topical antimicrobial agents against multidrug-resistant Pseudomonas aeruginosa infections. Similarly, no experimental study has investigated the effectiveness of citric acid against Pseudomonas aeruginosa infections in burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…Topical medications such as sulfamylon (mafenide acetate), silver nitrate, aquacel silver, Contreet antimicrobial foam, PolyMem Silver dressings, boric acid, acetic acid, 3% citric acid, 0.5% chlorhexidine acetate (Bactigrass), silver sulfadiazine 1% (Silverdin), and silver-coated dressing (Acticoat) are used clinically to treat Pseudomonas aeruginosa infections, which are frequently encountered in burn intensive care units and often lead to mortality. [12][13][14][15][16][17] Several topical and systemic antibacterial agents are used to treat infections in burn patients, and different drug groups produce distinct clinical responses. Most studies investigating such responses have examined topical agents individually.…”
mentioning
confidence: 99%